Unilateral ovarian recurrence 5 years after hysterectomy for microinvasive squamous cervical cancer stage IA1: a rare case report - Longxia Tong; Lin Wu (BMC, 2023)
Abstract Background Ovarian metastasis or recurrence of cervical microinvasive squamous cell carcinoma (SCC) is very rare. We report a case of unilateral ovarian recurrence 5 years after hysterectomy for the SCC stage IA1 without lymph vascular space invasion (LVSI). Case presentation A 49-year-old female patient suffered from a dull pain in the left lower abdomen for 3 months. And five years ago, she received a laparoscopic hysterectomy for the treatment of stage IA1 (without LVSI) SCC of the cervix. The level of squamous cell carcinoma antigen (SCC-Ag) in serum was significantly elevated (10.60 ng/mL). Pelvic magnetic resonance imaging (MRI) revealed a left ovarian solid tumor measuring 5.5 × 3.9 × 5.6 cm with heterogeneous enhancement. During laparotomy, the left ovarian tumor was measured about 5.0 × 4.5 × 3.0 cm and seemed densely adherent to the posterior peritoneal wall, including the left ureter. The tumor and pelvic lymph node were carefully removed. Postoperative anatomy revealed a solid mass with a greyish-white section. Postoperative pathology showed recurrent moderately differentiated ovarian SCC with negative pelvic lymph nodes. Immunohistochemistry showed that the tumor cells were positive for P16, P63, P40, and CK5/6 markers, and the positive rate of Ki67 was about 80%. Conclusions Ovary preservation is reasonable and appropriate in young patients with microinvasive SCC. Ovarian recurrence is rare, but gynecological oncologists should not overlook its possibility. The serum SCC-Ag is an important indicator for monitoring postoperative disease progression.